Sufism, Politics, and the Arab Spring (American Journal of Islam and Society, 2012)
This paper examines the role of Sufi individuals and groups in the politics of the Middle East and North Africa during and following the Arab Spring. While some have suggested that Sufis are distant from politics, this paper looks at events in Syria and Egypt, and how Sufis have been active in playing a political role in terms of calls for the dismissal of authoritarian leaders, as well as in the post-regime politics of the states. In the case of Syria, Muhammad al-Yaqoubi has taken a key role in advocating the removal of authoritarian regimes in the name of a democratic state. Similar calls have taken place in Egypt; in this case, Sufi groups have begun to form political parties for representation out of concern for the increase in political influence by the Muslim Brotherhood, as well as Salafi Muslim organizations.